2019
DOI: 10.1080/13607863.2019.1625303
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported needs and experiences of people with dementia living in nursing homes: a scoping review

Abstract: Objectives: With rates of dementia continuing to rise, the impetus on improving care for people with dementia is growing. Unmet needs of people with dementia living in nursing homes have been linked with worsening neuropsychiatric symptoms, higher levels of depression, and reduced quality of life. Furthermore, proxy accounts exploring the needs of people with dementia have frequently been shown to be unreliable. Therefore, this literature review aims to explore the selfreported needs and experiences of people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 71 publications
2
25
0
Order By: Relevance
“…People with dementia or aphasia may be limited to verbally express themselves or find it challenging recalling on past experiences; however, future studies should adopt an inclusive design by using a tailored approach for this population by, for example, using supportive visuals or observations (Alzheimer's Disease International, 2015; Curyto et al, 2008;Gardner et al, 1976;Scheffelaar, Hendriks, et al, 2018;Stans et al, 2013;Whitlatch, 2001). A recent review explored self-reported needs and experiences of people with dementia in nursing homes (Shiells et al, 2019). This is complementary to our review as it included qualitative and quantitative studies and focused on experiences, quality of life, and well-being expressed by people with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…People with dementia or aphasia may be limited to verbally express themselves or find it challenging recalling on past experiences; however, future studies should adopt an inclusive design by using a tailored approach for this population by, for example, using supportive visuals or observations (Alzheimer's Disease International, 2015; Curyto et al, 2008;Gardner et al, 1976;Scheffelaar, Hendriks, et al, 2018;Stans et al, 2013;Whitlatch, 2001). A recent review explored self-reported needs and experiences of people with dementia in nursing homes (Shiells et al, 2019). This is complementary to our review as it included qualitative and quantitative studies and focused on experiences, quality of life, and well-being expressed by people with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these calls to action, a recent scoping review of the needs and experiences of people living with dementia in nursing homes found that one of the most commonly occurring experiences of residents was boredom [13]. Furthermore, a recent study of people living with dementia in Norwegian care homes found that residents desired more opportunities for meaningful relations and activities [14].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of desired activities were identified in this study. One scoping review identified religious activities as one of the needs of PLwD [ 12 ]. However, in our study, religious activities were absent as daily life wishes.…”
Section: Discussionmentioning
confidence: 99%
“…The Alzheimer Europe promotes the engagement of PLwD in research that highlights the empowerment of PLwD in Patient and Public Involvement (PPI). Although researchers have emphasized the importance of including the direct voice of PLwD in the study, still very little is explored about the preferences of PLwD [ 12 ]. The limited literature in the area suggests that the perspectives of PLwD differ from those expressed by their caregivers/families and health professionals [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%